'This famous island is the home of freedom': Winston Churchill and the battle for 'European civilization'. Issue 5 (3rd July 2020) - Toye, Richard
ABSTRACT: This article explores the relationship between Churchill's view of Britain as the home of freedom and his broader conception of Western/European civilization. It considers: first, his attitude to Classical learning and culture; second, his experiences of European travel; and third, his attitude to the Bolsheviks (as much as the Nazis) as the barbaric antithesis of civilization. It is argued that his vision of the European future was linked both to his own experiences of free and civilized travel in the Nineteenth Century and a growing scepticism about the speedier and more globalized locomotion of the Twentieth. Moreover, Churchill's late-life commitment to the virtues of Classical learning, about which he had previously been sceptical, was connected to his post-WWII enthusiasm for European unity. He believed that a united Europe could act as a vehicle for spiritual and cultural values passed down from the ancient world which themselves had become a part of the continent's Christian heritage. Although it has rightly been pointed out that Churchill was not a conventional religious believer, he still conceived 'Christendom' as a significant geopolitical space (with flexible boundaries) and he saw it as the spiritual inheritor of Greece and Rome.